2005
DOI: 10.1081/pln-200055550
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Root Systems with Respect to Morphological Traits and Nitrogen-Absorbing Ability in the New Plant Type of Tropical Rice Lines

Abstract: The objective of this study was to characterize the root systems of the new plant type (NPT) of tropical rice (Oryza sative (L)) lines compared with the root system of IR72, one of the elite modern varieties. Two field experiments were conducted to observe plant growth under canopy conditions in the 1997 and 1998 wet seasons. In addition, a pot experiment was conducted in the 1998 dry season to observe plant growth under isolated conditions. The root systems of the NPT lines were characterized by roots heavier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…14). These observations suggest that the characteristics of the root systems in the new cultivars, in particular Takanari, might be attributed to the greater accumulation of nitrogen (Ookawa et al, 2004;San-oh et al, 2006b) although the increase in root dry weight and root length did not result in the promotion in nitrogen absorption in some cultivars (Samejima et al, 2005). This hypothesis remains to be confirmed.…”
Section: Plants Grown With Chemical Fertilizermentioning
confidence: 41%
“…14). These observations suggest that the characteristics of the root systems in the new cultivars, in particular Takanari, might be attributed to the greater accumulation of nitrogen (Ookawa et al, 2004;San-oh et al, 2006b) although the increase in root dry weight and root length did not result in the promotion in nitrogen absorption in some cultivars (Samejima et al, 2005). This hypothesis remains to be confirmed.…”
Section: Plants Grown With Chemical Fertilizermentioning
confidence: 41%
“…What morphological and physiological traits of roots should be for a high-yielding rice cultivar is still debating. Whether or not a larger root biomass and a stronger root activity would contribute to higher grain yield in rice remains an argument (Samejima et al, 2005;Yang et al, 2011). Earlier studies have showed that the rice root number, root weight, and root absorbing area were closely related with grain yield (Zhang et al, 2011(Zhang et al, , 2013Yang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We note here that several researchers have demonstrated that the greater efficiency of hybrid and 'super-rice' varieties is attributable in part to their genetic potential to maintain a higher rate of root oxidizing activity or delayed senescence of roots during later growth stages which translated into higher grain yield (Osaki et al 1997;Samejima et al 2005). Our present study showed, on the other hand, that management practices such as alternative water management and enhanced soil microbial density can also have significant effects on root development and roots' senescence rate, with subsequent impact on yield-influencing parameters.…”
Section: Introductionmentioning
confidence: 99%